NEURAL-NETWORK BASED METHOD OF CONTROL INFLUENCES FORMING IN COMPUTER SYSTEM CONTROLLING ENVIRONMENTAL PARAMETERS - Turchenko, Iryna (International Journal of Computing, 2014)
A simulation model of a section of mine ventilation network is considered in this paper. The simulation modeling of transient aerogasdynamic processes of methane concentration changing is fulfilled at applying position and exponential control influences. There is proposed a neural-based method of control influences forming by neural network training on the set of optimal control influences. There are defined a criterion and developed an algorithm of optimal control influences forming as a training set of neural network. The simulation modeling of applying of control influences formed by neural network is fulfilled and decreasing of control parameter in the section of mine ventilation network is estimated.